RelA-SpoT Homolog toxins pyrophosphorylate the CCA end of tRNA to inhibit protein synthesis - Kurata, Tatsuaki; Brodiazhenko, Tetiana; Alves Oliveira, Sofia Raquel; Roghanian, Mohammad; Sakaguchi, Yuriko; Turnbull, Kathryn Jane; Bulvas, Ondřej; Takada, Hiraku; Tamman, Hedvig; Ainelo, Andres; Pohl, Radek; Rejman, Dominik; et al. (Molecular cell, 2021)
RelA-SpoT Homolog (RSH) enzymes control bacterial physiology through synthesis and degradation of the nucleotide alarmone (p)ppGpp. We recently discovered multiple families of small alarmone synthetase (SAS) RSH acting as toxins of toxin-antitoxin (TA) modules, with the FaRel subfamily of toxSAS abrogating bacterial growth by producing an analog of (p)ppGpp, (pp)pApp. Here we probe the mechanism of growth arrest used by four experimentally unexplored subfamilies of toxSAS: FaRel2, PhRel, PhRel2, and CapRel. Surprisingly, all these toxins specifically inhibit protein synthesis. To do so, they transfer a pyrophosphate moiety from ATP to the tRNA 3' CCA. The modification inhibits both tRNA aminoacylation and the sensing of cellular amino acid starvation by the ribosome-associated RSH RelA. Conversely, we show that some small alarmone hydrolase (SAH) RSH enzymes can reverse the pyrophosphorylation of tRNA to counter the growth inhibition by toxSAS. Collectively, we establish RSHs as RNA-modifying enzymes.
Keywords: Phosphorylation; inhibitory syntézy proteinů; RNA, Transfer; fosforylace; ribozomy; Protein Synthesis Inhibitors; Gram-Positive Asporogenous Rods; Ribosomes; RNA transferová; proteosyntéza; Guanosine Pentaphosphate; Ligases; pyrofosfatasy; guanosinpentafosfát; Bacterial Toxins; grampozitivní nesporulující tyčinky; bakteriální toxiny; Protein Biosynthesis; ligasy; Pyrophosphatases